Effects of average reward rate on vigor as a function of individual variation in striatal dopamine. - Hofmans, Lieke; Westbrook, Andrew; van den Bosch, Ruben; Booij, Jan; Verkes, Robbert-Jan; Cools, Roshan (Psychopharmacology, 2022)
Rationale: We constantly need to decide not only which actions to perform, but also how vigorously to perform them. In agreement with an earlier theoretical model, it has been shown that a significant portion of the variance in our action vigor can be explained by the average rate of rewards received for that action. Moreover, this invigorating effect of average reward rate was shown to vary with within-subject changes in dopamine, both in human individuals and experimental rodents. Objectives: Here, we assessed whether individual differences in the effect of average reward rate on vigor are related to individual variation in a stable measure of striatal dopamine function in healthy, unmedicated participants. Methods: Forty-four participants performed a discrimination task to test the effect of average reward rate on response times to index vigor and completed an [18F]-DOPA PET scan to index striatal dopamine synthesis capacity. Results: We did not find an interaction between dopamine synthesis capacity and average reward rate across the entire group. However, a post hoc analysis revealed that participants with higher striatal dopamine synthesis capacity, particularly in the nucleus accumbens, exhibited a stronger invigorating effect of average reward rate among the 30 slowest participants. Conclusions: Our findings provide converging evidence for a role of striatal dopamine in average reward rate signaling, thereby extending the current literature on the mechanistic link between average reward rate, vigor, and dopamine.